Electrical contacts to single nanowires: a scalable method allowing multiple devices on a chip. Application to a single nanowire radial p–i–n junction. (29th April 2013) - Blanc, Pierre; Heiss, Martin; Colombo, Carlo; Mallorquì, Anna Dalmau; Safaei, Tina Saberi; Krogstrup, Peter; Nygård, Jesper; Morral, Anna Fontcuberta i
Semiconductor nanowires are currently at the forefront of research in the areas of nanoelectronics and energy conversion. In all these studies, realising electrical contacts and statistically relevant measurements is a key issue. We propose a method that enables to contact hundreds of nanowires on a single wafer in an extremely fast electron beam lithography session. The method is applied to nanowire–based radial GaAs p–i–n junction. Current–voltage characteristics are shown, along with scanning photocurrent mapping.